Identifikasi Potensi Sumberdaya Pesisir Desa Semare Untuk Pemberdayaan Masyarakat Menuju Desa Mandiri Wisata - Maftuch Maftuch (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
Semare village has a mangrove forest area and as a place to develop pond fisheries refers to the regional development policy outlined in the RTRW. Based on existing economic potential data, it can be said that the basic capital of developing shellfish and crab commodity based tourism villages in the village Semare is available and can be said to be quite adequate. One of the obstacles faced in developing culinary tourism in Semare Village is settlement arrangement and environmental cleanliness. The acceleration and increase in the intensity of the interaction between the residents of Semare Village and the outside world through the development of Shellfish and Crab Commodity-Based Tourism Villages is expected to accelerate the welfare improvement of the residents of Semare Village. Tourism development was chosen as the main strategy to improve community welfare because the characteristics of tourism businesses are to use local potential and always provide added value to local products while opening up markets for local products through direct selling to end customers.